Squamous Cell Carcinoma Companionship With Fanconi Anemia: Rare Situation or Increasing Hazard?. Issue 5 (September 2017) - Navabazam, Alireza; Forat Yazdi, Mohammad; Keyhan, Seied Omid; Ghanean, Sina; Amirzade-Iranaq, Mohammad Hosein
Abstract: The increased susceptibility of malignancies in Fanconi Anemia (FA), an autosomal recessive disease, is a major concern of this syndrome. According to previous reports, Head and neck squamous cell carcinoma (HNSCC) is one of the most frequently diagnosed solid tumors in these patients. Herein the authors report a unique case of HNSCC in the hard palate of a 31-year old female patient with FA syndrome, which was treated by surgical removal. Additionally, the literature about Squamous Cell Carcinoma companionship with Fanconi Anemia is reviewed.